Analysing adipokine Omentin-1 in periodontal disease and type-2 diabetes mellitus: An interventional comparative study - Avexilla Dooxa Nongrum; Sanjeela R. Guru; Nisha K J; Suchetha Aghanashini (Journal of Oral Biology and Craniofacial Research)
Background and objective: Omentin-1 is an anti-inflammatory adipokine associated with metabolic disorders including insulin resistance, glucose intolerance and type 2 diabetes mellitus (T2DM). Diabetes is a crucial systemic risk factor for occurrence of periodontitis. Periodontitis is deliberated as a complication of diabetes. This study aimed to estimate salivary and serum levels of Omentin-1 in chronic periodontitis with or without diabetes mellitus before and after scaling and root planing (SRP) and also the level of glycemic control. Materials and methods: Based on history and clinical parameters, 70 subjects were allocated into two groups i.e. chronic periodontitis (Group 1) and chronic periodontitis with well controlled T2DM (Group 2). Baseline saliva and serum samples were collected from both groups followed by full mouth SRP. Subjects were recalled 3 months post SRP for salivary and serum sample collection and measurement of clinical parameters. Serum as well as salivary samples collected were further analysed using enzyme-linked immunosorbent assay to determine the Omentin-1 concentration in each sample. Results: The levels of Omentin-1 in saliva and serum were significantly lower in both the groups at baseline. Clinical parameters exhibited a significant reduction 3 months post SRP in both groups. Salivary and serum Omentin-1 levels significantly increased in both the groups, 3 months post SRP. HbA1c levels also reduced significantly post therapy. Conclusion: A significant relation exists between salivary and serum Omentin-1 in chronic periodontitis and chronic periodontitis with T2DM. In consequence, Omentin-1 level can have possible application as inflammatory marker of T2DM, periodontal disease and treatment outcome.